2019
DOI: 10.4062/biomolther.2017.260
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Mesenchymal Stem Cells in Tissue Regeneration and Immunomodulation

Abstract: Mesenchymal stem cells are classified as multipotent stem cells, due to their capability to transdifferentiate into various lineages that develop from mesoderm. Their popular appeal as cell-based therapy was initially based on the idea of their ability to restore tissue because of their differentiation potential ; however, the lack of evidence of their differentiation to target cells led researchers to focus on their secreted trophic factors and their role as potential powerhouses on regulation of factors unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 82 publications
1
89
0
2
Order By: Relevance
“…Engela et al demonstrated that Treg cells can induce IDO secretion in MSCs, which results in TNF-α reduction and induction of IL-10 in Treg cells and effector cells [286]. Different subtypes of Treg cells generated by MSCs have been identified including CD4 + CD25 + Foxp3 + Treg cells and IL-10 producing type 1 Treg (Tr1) cells [287]. There is a complex cross-talk between MSCs and macrophages, which cannot be simply explained by MSCderived anti-inflammatory factors.…”
Section: The Target Cell Profilementioning
confidence: 99%
“…Engela et al demonstrated that Treg cells can induce IDO secretion in MSCs, which results in TNF-α reduction and induction of IL-10 in Treg cells and effector cells [286]. Different subtypes of Treg cells generated by MSCs have been identified including CD4 + CD25 + Foxp3 + Treg cells and IL-10 producing type 1 Treg (Tr1) cells [287]. There is a complex cross-talk between MSCs and macrophages, which cannot be simply explained by MSCderived anti-inflammatory factors.…”
Section: The Target Cell Profilementioning
confidence: 99%
“…One cell type, in particular, under intense investigation for its potential utility in the treatment of a variety of human diseases are mesenchymal stromal cells (MSCs). The interest in MSC therapy is largely due to their accessibility from adult tissue, their multilineage differentiation potential, and their diverse mechanism of action through both cryoprotective and paracrine effects, as well as their low immunogenicity [ 14 , 15 , 16 ].…”
Section: Cellular Therapymentioning
confidence: 99%
“…研究发现, MSC产生的生物活性物质参与 Figure 2 Bioactive substances produced by MSCs [27] 是通过一氧化氮合成酶(inducible nitric oxide synthase, iNOS)产生大量NO在抑制淋巴细胞活性方面发挥关 键作用 [28] . MSCs产生的多种免疫调节因子之间可通 过协同或拮抗发挥作用, 不仅参与免疫反应的调控, 而且还参与炎症反应的应答和组织损伤修复等多个生 物学进程 [29,30] .…”
Section: 伤部位 通过旁分泌作用激活组织内源特异性干/祖细unclassified